Application of Server Virtualization Technology in Power Information Construction. Issue 2 (February 2021) - Yu, Hai; Guo, Jing; Wu, Lei; Wu, Shun; Peng, Bo
Abstract: In recent years, with the development of our country, higher requirements are put forward for the power supply. Electric power enterprises want to improve their comprehensive strength, but also in order to adapt to the development of the times, it is necessary to carry out information construction. However, the traditional physical server has many shortcomings and shortcomings in the enterprise information construction. Therefore, this paper puts forward the application research of server virtualization technology in power information construction. This paper compares and analyzes the resources needed by physical server and virtual server, and points out that virtual server have obvious advantages of high information security, low energy consumption, high utilization rate and low maintenance cost. In order to make the virtual server successfully applied in the information construction of electric power enterprises, this paper puts forward the operation guidance standard of server virtualization implementation process, and emphasizes that the integration of server resources should be done well in the process of information construction. In order to ensure the security of server virtualization process, this paper lists the detailed security measures of server virtualization. According to the operation of the above steps, the power enterprise can complete the information construction work better through the virtualization of the server. It is considered that the use of virtual server in enterprise information construction is a big trend, which conforms to the development of the times and improves the utilization rate of resources.